Preparation of a New AAC-Concrete Sandwich Block and its Compressive Behavior at Quasi-Static Loading - ABED, Farid; AIDAN, Ahmed; IBRAHIM, Taleb; HEGAZI, Nouran; AL-DABAGH, Saif (Engineering Transactions, 2017)
Autoclaved aerated concrete (AAC) is an environmentally friendly material that has several advantages such as heat insulation, sound insulation, and light weight which reduce the energy consumption of a structure during its construction and when using it. However, the compressive strength of AAC is relatively low in comparison with concrete masonry units that are used as building blocks. This paper provides insight into a newly proposed AAC-concrete sandwich composite. The main aim of this research is to produce a lightweight eco-friendly loadbearing building block. Construction and demolition wastes including the cement and fine powder waste were utilized to generate the AAC-concrete composite. The proposed sandwich composite was tested in a number of stages. Firstly, a preliminary test was conducted to test the proposed sandwiching technique. Three sets of plain sandwich specimens were prepared, each with a different combination of AAC thickness and concrete thickness. It was found that the proposed composite had a higher compressive strength than AAC and a lower density than the normal concrete. Secondly, different concrete and mortar mixes were prepared and studied to identify the mix that would yield the best sandwich composite. This best mix was identified and used throughout the experiment. Thirdly, different sandwiching techniques were applied to enhance bonding at the AAC-concrete interface. The proposed sandwiching techniques were as follows: (1) inserting grooves at the AAC-concrete interface and (2) wrapping the AAC block with wire mesh. Multiple cube specimens with 10 cm side length were prepared and tested for their compressive strength. It was found that the wire mesh provided a more effective bonding. Finally, additional grooved and plain sandwich cube specimens with 20 cm side length were prepared and tested under different quasi-static loading rates. Unlike plain sandwich block, the compressive behavior of grooved sandwich showed a slight increase in its capacity at higher quasi-static rate. Almost all specimens in this study failed in a similar manner that is, by debonding at the AAC-concrete interface, followed by crushing.